Marginal and internal fit and intaglio surface trueness of interim crowns fabricated from tooth preparation of four finish line locations - Keunbada Son (Nature Portfolio, 2021)
Abstract This study evaluated the marginal and internal fit and intaglio surface trueness of interim crowns fabricated from tooth preparation scanned at four finish line locations. The right maxillary first molar tooth preparation model was fabricated using a ceramic material and placed in four finish line locations (supragingival, equigingival, subgingival, and subgingival with a cord). Intraoral scanning was performed. Crowns were designed based on the scanned area. Interim crowns were fabricated using a stereolithography three-dimensional (3D) printer (N = 16 per location). Marginal and internal fit were evaluated with a silicone replica technique. Intaglio surface trueness was evaluated using a 3D inspection software. One-way analysis of variance and Tukey HSD test were performed for comparisons (α = 0.05). The marginal and internal fit showed significant differences according to locations (P < 0.05); the marginal fit showed the best results in the supragingival finish line (P < 0.05). Intaglio surface trueness was significantly different in the marginal region, with the highest value in the subgingival location (P < 0.05). Crowns fabricated on the subgingival finish line caused inaccurate marginal fit due to poor fabrication reproducibility of the marginal region. The use of an intraoral scanner should be decided on the clinical situation and needs.